Impact of agro-environmental systems on soil erosion processes and soil properties on hilly landscape in Western Lithuania - Jarašiūnas, Gintaras; Kinderienė, Irena (Journal of Environmental Engineering and Landscape Management, 2016)
The objective of this study was to evaluate the impact of different land use systems on soil erosion rates, surface evolution processes and physico-chemical properties on a moraine hilly topography in Lithuania. The soil of the experimental site is Bathihypogleyi – Eutric Albeluvisols (abe–gld–w) whose texture is a sandy loam. After a 27-year use of different land conservation systems, three critical slope segments (slightly eroded, active erosion and accumulation) were formed. Soil physical properties of the soil texture and particle sizes distribution were examined. Chemical properties analysed for were soil ph, available phosphorus (P) and potassium (K), soil organic carbon (SOC) and total nitrogen (N). We estimated the variation in thickness of the soil Ap horizon and soil physico-chemical properties prone to a sustained erosion process. During the study period (2010–2012) water erosion occurred under the grain– grass and grass–grain crop rotations, at rates of 1.38 and 0.11 m3 ha–1 yr–1, respectively. Soil exhumed due to erosion from elevated positions accumulated in the slope bottom. As a result, topographic transfiguration of hills and changes in soil properties occurred. However, the accumulation segments of slopes had significantly higher silt/clay ratios and SOC content. In the active erosion segments a lighter soil texture and lower soil ph were recorded. Only long-term grassland completely stopped soil erosion effects; therefore geomorphologic change and degradation of hills was estimated there as minimal.First published online: 19 Oct 2015